The impact of Undetectable=Untransmittable and viral suppression on condomless sex among mixed HIV-status couples in Canada - Min Xi; Sandra Bullock; Joshua B. Mendelsohn; Veronika Moravan; Ann N. Burchell; Darrell H. S. Tan; Bertrand Lebouché; Jean-Pierre Routy; Amrita Daftary; Tamara Thompson; Liviana Calzavara (PLoS ONE, 2025)
Introduction/Objectives Undetectable = Untransmittable (U = U) means that virally suppressed HIV-positive partners cannot transmit HIV. With advancements in HIV care and the increasing number of mixed HIV-status relationships, we quantified U = U agreement (agreeing/disagreeing that U = U is true) among people in mixed HIV-status relationships, assessed response concordance between partners, quantified the association between dyad-level U = U agreement and condomless sex, and estimated interaction effects of viral suppression. Methods A cross-sectional opportunistic and snowball sampled survey explored condom use, U = U agreement, viral suppression, sociodemographic/relationship characteristics, and sexual behavior among 306 participants (153 matched dyads) in mixed HIV-status relationships (2016–2018). Bivariate analyses identified sociodemographic/relationship characteristics associated with U = U agreement. Cohen’s Kappa assessed response concordance between partners. Firth logistic regression estimated associations between dyad-level U = U agreement and condomless sex with effect modification by viral suppression. Results Of 293 responses to the U = U question, 53.2% agreed with U = U. Agreement was associated with younger age (p = 0.006) and shorter duration of HIV in relationships (p = 0.034). Concordance between partners was higher for factual questions (kappa>0.50) and lower for belief/decision-making questions (kappa<0.40). The predicted probability of always having condomless sex was 0.60 (95% CI:0.57,0.64) when dyads agreed with U = U and the HIV-positive partner was virally suppressed. The likelihood of always having condomless sex was low when the HIV-positive partner was not virally suppressed, whether or not dyads agreed with U = U (predicted probability range: 0.08;95% CI:0.06,0.11 to 0.25;95% CI:0.17,0.33), or when only one partner agreed with U = U (predicted probability range:0.02;95% CI:0.01,0.02 to 0.11;95% CI:0.07,0.15). Conclusions Dyad-level U = U agreement, viral suppression, and views of both partners were key factors in mixed HIV-status couples’ decisions to have condomless sex. Future representative studies among sexual identity and racialized minority sub-populations are needed to better understand how mixed HIV-status relationships receive and apply U = U messaging, with a focus on partner age and the duration of HIV within relationships.